Culture versus PCR for Salmonella Species Identification in Some Dairy Products and Dairy Handlers with Special Concern to Its Zoonotic Importance - Mayada M. Gwida; Maha A. M. AL-Ashmawy (Veterinary Medicine International)
A total of 200 samples of milk and dairy products as well as 120 samples of dairy handlers were randomly collected from different dairy farms and supermarkets in Dakahlia Governorate, Egypt. The conventional cultural and serotyping methods for detection of Salmonella in dairy products were applied and the results were compared with those obtained by molecular screening assay using (ttr sequence). The obtained results revealed that 21% of milk and dairy products (42/200) were positive for Salmonella species using enrichment culture-based PCR method, while 12% of different dairy samples (24/200) were found to be positive for Salmonella species by using the conventional culture methods. Two stool specimens out of 40 apparently healthy dairy handlers were positive by the PCR method. Serotyping of Salmonella isolates revealed that 58.3% (14/24) from different dairy products were contaminated with Salmonella Typhimurium. We conclude that the enrichment culture-based PCR assay has high sensitivity and specificity for detection of Salmonella species in dairy products and handlers. High incidence of Salmonella Typhimurium in the examined dairy samples highlights the important role played by milk and dairy products as a vehicle in disease prevalence. Great effort should be applied for reducing foodborne risk for consumers.